Social potential of professional guidance work with minors on the example of military-patriotic activities of Ministry of Internal Affairs of the Republic of Belarus - Himmelreich, Oleg V. (Journal of the Belarusian State University. Sociology, 2026)
The article explores the social potential of vocational guidance (using the example of the organisation of military-patriotic activities in the Ministry of Internal Affairs of the Republic of Belarus system), as well as its impact on the formation of a conscious need to choose a specific profession. The article reveals the goals, objectives, and content of interest clubs (military-patriotic clubs) as a social environment that fosters the development of prosocial qualities in children and young people, as well as the internalisation of patriotic and spiritual values supported by the state and society. It is noted that the potential of the military-industrial complex contributes to the development of communication skills and the realisation of social expectations, and ultimately to professional self-determination. It is concluded that the formation of needs and motives (based on beliefs) for a conscious choice of a profession that serves society and the state occurs according to the scheme «familiarisation – assimilation – participation – accumulation of social experience – principle».